Praktek Pemberian Makan Bayi dan Anak Berdasarkan Daerah Tempat Tinggal di Provinsi Bengkulu, Indonesia: Infant and Young Child Feeding Practices Based on Region of Residence in Bengkulu Province, Indonesia - Simbolon, Demsa; Suryani, Desri; Yunita, Yunita; Fauzi, Yusran (Universitas Airlangga, 2025)
Background: Children under two years old go through a rapid physical growth period, requiring the highest nutritional intake compared to other age groups. However, infant and young child feeding (IYCF) practices are often suboptimal, leading to nutritional and health problems. Objectives: This study aimed to determine the determinants of IYCF practices in Bengkulu Province. Methods: The study used a cross-sectional design from the 2017 IDHS data. The sample was women of childbearing age 15-49 years who had children aged 6-24 months, as many as 73 children with a stratified two-stage sampling technique. Data analysis using proportion difference test with chi-square test and multivariate binary logistic regression. Results: This study found that in 83.9% of urban areas and 91.5% of rural areas, the practice of IYCF is not by the recommendations. There is no difference in IYCF practice between urban and rural areas. Factors related to the practice of IYCF are pregnancy planning and antenatal care (ANC) quantity. Unplanned pregnancies had a risk of 4.8 times (p-value=0.04) the practice of IYCF was not as recommended compared to the intended pregnancies. The quantity of antenatal care that was not at risk was 4.8 times the practice of IYCF was not as recommended compared to the quantity of good ANC (p-value=0.05). Conclusions: Pregnancy planning needs to be educational material for young women, and an increase in efforts to increase knowledge of pregnant women about IYCF during antenatal care through nutrition counseling programs or classes for pregnant women in health facilities.